Caffeine use in sports. A pharmacological review - Sinclair, C. J.; Geiger, J. D. (The Journal of Sports Medicine and Physical Fitness, 2000)
Caffeine is the most widely ingested psychoactive drug in the world. As many know, chronic use of caffeine leads to dependence, tolerance, drug craving, and upon abrupt cessation unpleasant withdrawal symptoms. Thus, caffeine fulfills pharmacological criteria by which agents are classified as drugs of abuse. Nevertheless, its use is legal and only at high, but readily attainable, levels is it banned from sport. Its use is widespread by athletes as young as 11 years of age who are seeking athletic advantage over fellow competitors. It is likely that its use will not decline any time soon because it is inexpensive, readily available, medically quite safe, socially acceptable, and by most measures legal. However, at levels allowed in sport, caffeine through its wide-ranging physiological and psychological effects increases endurance in well-trained athletes. If the goal of drug-testing and education programs in sport is to protect the health of athletes, prevent unfair advantage (cheating) and encourage ethical behavior then it seems obvious that the allowable levels of caffeine ingestion should be decreased. The alternative is to continue with policies designed largely to punish only those that get caught.